Characterization of genetic context of blaKPC in Pseudomonas aeruginosa - Chen, Mingxiao; Deng, Tingting; Li, Xiaobin; Zhou, Runcheng; Gao, Zhangshu; Zhou, Die; Zhu, Jianqiang; Li, Jingjie; Chen, Xin; Wang, Minling; Zhang, Rui; Zhou, Qiang (Frontiers in Microbiology, 2025)
The rising prevalence of blaKPC-harboring Pseudomonas aeruginosa (KPC-PA) is a significant threat to public health. In the study, we identified a carbapenem-resistant P. aeruginosa (CRPA; PAE3) from a patient with pneumonia infection. The resistance phenotype was analyzed using the broth microdilution method. Whole-genome sequencing was performed to sequence type (ST), resistance genes, plasmid replicon, and the genetic environment of the blaKPC-2 gene. The other 75 Pseudomonas aeruginosa (PA) isolates with chromosome- or plasmid-borne blaKPC gene were used to analyze the mobilized characterization of blaKPC gene in PA from a global perspective. The result revealed PAE3 belonged to ST463 and exhibited multidrug resistance, which is the first report of PA harboring a chromosome-borne blaKPC-2 gene located within a Tn1721-like transposon in South China. In total, 76 KPC-PA strains were identified from 7 countries, representing 6 distinct blaKPC variants—blaKPC-2, blaKPC-3, blaKPC-33, blaKPC-87, blaKPC-90, and blaKPC-113—with the majority located within transposons such as Tn1403, Tn1721, Tn4401, or Tn6296-like elements. A total of 63 blaKPC-positive plasmids evolved into different phylogenetic clades in China and other countries, indicating clonal transmission and regional evolution. The dissemination of blaKPC is primarily observed in three distinct forms in ST463 KPC-PA in China: (1) plasmid-mediated transfer associated with Tn6296-like transposon; (2) Tn1721, and (3) the IS26-ISKpn27-blaKPC-2-ISKpn6 structural arrangement, which is integrated into both plasmid and chromosome. In contrast, Tn4401 is commonly observed in Europe and the United States, predominantly emerging in ST235. This study represents the valuable systematic classification of the transposons associated with the spread of blaKPC and offers new insights into the mobilized genetic platforms that contributed to the global dissemination of carbapenem resistance in PA.